Differential Expression Profile of microRNAs and Tight Junction in the Lung Tissues of Rat With Mitomycin-C-Induced Pulmonary Veno-Occlusive Disease - Song, Qing; Chen, Ping; Wu, Shang-Jie; Chen, Yan; Zhang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Background Pulmonary veno-occlusive disease (PVOD) is characterized by increased pulmonary vascular resistance. Currently, there is a lack of effective treatment. It is of great significance to explore molecular targets for treatment. This study investigated the differential expression profile of miRNAs and tight junction in the lung tissues of rats with mitomycin-C (MMC)-induced PVOD. Methods A total of 14 rats were divided into the control group and he PVOD group. We measured mean pulmonary arterial pressure (mPAP) and right ventricular hypertrophy index (RVHI). Pathological changes including those in lung tissues, pulmonary venules, and capillary were detected by H&E and orcein staining. Western blot was used to detect GCN2, ZO-1, occludin, and claudin-5 expression. We analyzed the miRNAs profile in the rat lung tissues by high-throughput sequencing. The top differentially expressed miRNAs were validated by using real-time polymerase chain reaction (RT-PCR). Results There were severe pulmonary artery hypertrophy/hyperplasia, thickening, and occlusion in the small pulmonary veins, pulmonary edema, and dilated capillaries in MMC-induced rats with PVOD. In addition, mPAP and RVHI were significantly increased (P < 0.05). The expression of GCN2 was significantly decreased (P < 0.05). A total of 106 differentially expressed miRNAs were identified. According to the fold changes, the top ten upregulated miRNAs were miRNA-543-3p, miRNA-802-5p, miRNA-493-3p, miRNA-539-3p, miRNA-495, miRNA-380-5p, miRNA-214-5p, miRNA-539-5p, miRNA-190a-3p, and miRNA-431. The top 10 downregulated miRNAs were miRNA-201-3p, miRNA-141-3p, miRNA-1912-3p, miRNA-500-5p, miRNA-3585-5p, miRNA-448-3p, miRNA-509-5p, miRNA-3585-3p, miRNA-449c-5p, and miRNA-509-3p. RT-PCR confirmed that miRNA-214-5p was upregulated, while miRNA-141-3p was downregulated (P < 0.05). Functional analysis showed various signaling pathways and metabolic processes, such as fatty acid biosynthesis, tight junction, and the mTOR signaling pathway. In addition, the expression of the tight junction-related protein of ZO-1, occludin, and claudin-5 was significantly decreased in rats with PVOD (P < 0.05). Conclusion miRNAs may be involved in the pathogenesis of PVOD. Furthermore, ZO-1, occludin, and claudin-5 verification confirmed that the tight junction may be involved in the development of the disease.